Penulisan Naskah Program Berkah Islami di Kompas TV Jawa Tengah - Istiqomah Sheyla Al Kautsar; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Television is still ranked as the highest mass media consumed by the public. The development of the increasingly rapid television industry also invited local television to take part in filling Indonesia's glass screens. One of the local television stations in Central Java, especially Semarang, which still exists on air until now is Kompas TV in Central Java. Kompas TV Jawa Tengah became a television station that featured news programs and information that were accurate, fast, informative, trusted, educating and inspiring. The making of the Berkah Islami program stems from the lack of religious programs that raise adab and sunnah regarding minor issues in human daily life based on the Koran and Hadith which are discussed lightly and can be applied so that they are easily understood by the public. So that it becomes a challenge for the script writer to pour his ideas into a piece of paper that is presented in accordance with good writing procedures for television programs, so that the content presented in a program can be a reference and make it easier for all parties involved in the execution process both in front or behind the scenes to produce shows that are interesting, informative, and can educate the public. The